2021
DOI: 10.1007/s10549-021-06276-7
|View full text |Cite
|
Sign up to set email alerts
|

A 95-gene signature stratifies recurrence risk of invasive disease in ER-positive, HER2-negative, node-negative breast cancer with intermediate 21-gene signature recurrence scores

Abstract: Purpose A subset of patients with intermediate 21-gene signature assay recurrence score may bene t from adjuvant chemoendocrine therapy, but a predictive strategy is needed to identify such patients. The 95-gene signature assay was tested to stratify patients with intermediate RS into high (95GC-H) and low (95GC-L) groups that were associated with invasive recurrence risk.Methods Patients with ER-positive, HER2-negative, node-negative breast cancer and RS 11-25 who underwent de nitive surgery and adjuvant endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…Finally, all study participants were Japanese, and the performance when targeting other races in other countries is unknown. However, a recently published study evaluated the recurrence stratification of patients from both Japan and the US, with comparable results between populations [17].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, all study participants were Japanese, and the performance when targeting other races in other countries is unknown. However, a recently published study evaluated the recurrence stratification of patients from both Japan and the US, with comparable results between populations [17].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a 95-gene signature assay (Curebest 95GC Breast, Sysmex Corporation, Kobe, Japan), which stratifies patients into high (95GC-H) and low (95GC-L) groups, is used to predict recurrence risk in ESBC patients with ER+, HER2−, and lymph node negative (N0). Curebest 95GC assay has helped reduce the unnecessary administration of ACT [ 15 ]. A previous study has also demonstrated that the patients with ER+, HER2−, and N0 have less aggressiveness, and 85% did not experience recurrence [ 14 ].…”
Section: Adjuvant Chemotherapy (Act)mentioning
confidence: 99%
“…Yao L et al reported that breast cancer patients with HER2+ or TNBC benefited from standard NACT cycles [ 21 ]. Breast cancer patients with the most common type (i.e., invasive ductal carcinoma) at low risk (RS < 10) did not benefit from receiving NACT except AET [ 15 ]. Soliman H et al generated the RS among 764 ER+, HER2− breast cancer patients with Oncotype DX test results and compared to their ability to predict pCR to NACT.…”
Section: Neoadjuvant Chemotherapy (Nact)mentioning
confidence: 99%
See 2 more Smart Citations